842 Multi-centre implementation of the SNAP Protocol for paracetamol overdose – fewer anaphylactoid reactions and shortened length of stay. Issue 3 (21st February 2022) - Joseph, Roshan; Manning, William; Hemavathi, Muniswamy; Austin, Richard
Abstract : Aims/Objectives/Background: Paracetamol overdose is the most common drug overdose in the UK. The standard treatment of Paracetamol toxicity is intravenous N-acetylcysteine (NAC) which is usually given as a 21-hour infusion in UK hospitals. A 12-hour infusion known as the 'SNAP' regimen has been implemented in some centres and appears on TOXBASE. The SNAP regimen has been associated with fewer anaphylactoid reactions than the standard 21-hour treatment. The SNAP regimen was initiated in two District General Hospital Emergency Departments within the same NHS Trust as part of a quality improvement project (QIP) to determine whether anaphylactoid reactions and inpatient length of stay could be reduced. Methods/Design: Trust guidelines for Paracetamol overdose were revised advising the 12-hour SNAP regimen for treatment of adults along with a pre-filled prescription chart. A retrospective review of patient notes and electronic discharge letters was performed before and following the new guideline to identify patients who received NAC and whether they suffered any adverse reactions. The length of stay was also recorded. Results/Conclusions: In three months from August to November 2020, across both sites, 60 adult patients received NAC for Paracetamol overdose. Of these, four patients had anaphylactoid reactions to NAC. Following the introduction of the SNAP regimen, in three months between April and June 2021, 36 adult patients received NAC, and there were no adverse drug reactions. Prior to the introduction of the new guideline and prescription chart adult patients admitted for Paracetamol overdose had an average inpatient stay of 48.3 hours compared to an average stay of 44.5 hours following the introduction of the SNAP regimen. The SNAP NAC regimen was not associated with more adverse drug reactions and has decreased length of stay in adult inpatients with Paracetamol Overdose.